Penggunaan Tindakan Keras Sebagai Upaya Diskresi Kepolisian Dalam Penangkapan Tersangka Tindak Pindana Terorisme - Anggraini, Yasinta, Sudaryono,SH., M.HUM (2017)
Law enforcement officials, especially the police can do a discretion or authority to act according to his own judgment in carrying out other actions based on their authority to carry out a crackdown on an alleged criminal act of terrorism in the public interest under Article 18 of Law No. 2 of 2002 on the Indonesian National Police. The crackdown carried out by police during arrests of suspected criminal acts of terrorism under the rules of law, it is permissible if it meets the elements that already exist in the provisions of the legislation. Use of force in policing actions stipulated in the Indonesian National Police Chief, No. 1 of 2009 on the Use of Force in police action. As a reference use any members of the police, including the Special Detachment (Densus) 88 Anti Terror in the execution of their duties in the field oriented Human Rights (HAM) regulated under Police Chief Regulation No. 8 of 2009 on the Implementation of Standards and Human Rights in the Implementation The task of the Indonesian National Police.